Toxicological Evaluation of Kenaf Seed Supercritical Carbon Dioxide-Oil in Male Sprague Dawley Rats - Siti Aisyah Abd Ghafar; Latifah Saiful Yazan; Sharida Fakhurazi; Maznah Ismail (ASM Science Journal, 2021)
Kenaf seed supercritical carbon dioxide oil (KSO-SFE) is known for its numerous health benefits such as high antioxidant activity, lower plasma cholesterol level, chemopreventive to cervical and colon cancer. As there has been no report of toxicological evaluation, present study was conducted to assess the toxicity effects of KSO-SFE at 500, 1000, 1500 mg/kg body weight/day on male Sprague Dawley rats for 90 days. Parameters measured were body and organs weight, hematology, serum biochemistry, and histopathology of liver and kidneys. Induction with KSO-SFE showed lower creatinine level at all doses when compared with control group. Whereas lower plasma cholesterol level has been observed at 1000 and 1500 mg/kg bw/day, respectively. These slight changes were considered no toxicological significance. No mortality or treatment-related adverse effects in any of the parameters measured throughout the administration period even at the highest dose (1500 mg/kg bw). Based on these results, the no-adverse-effect level (NOAEL) for KSO-SFE under the condition of this study corresponds to the highest dose (1500 mg/kg bw/day).